2018
DOI: 10.1074/jbc.ra118.003145
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin is a natural inhibitor of plasminogen activation

Abstract: The plasminogen system is essential for dissolution of fibrin clots, and in addition, it is involved in a wide variety of other physiological processes, including proteolytic activation of growth factors, cell migration, and removal of protein aggregates. On the other hand, uncontrolled plasminogen activation contributes to many pathological processes ( tumor cells' invasion in cancer progression). Moreover, some virulent bacterial species ( or ) bind human plasminogen and hijack the host's plasminogen system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 62 publications
1
44
0
Order By: Relevance
“…Lf can exert negative regulatory effects on cell migration via inhibition of plasminogen activation and through the regulation of fibrinolysis (Zwirzitz et al, 2018). In addition, we observed an increased platelet count after Lf treatment.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Lf can exert negative regulatory effects on cell migration via inhibition of plasminogen activation and through the regulation of fibrinolysis (Zwirzitz et al, 2018). In addition, we observed an increased platelet count after Lf treatment.…”
Section: Discussionmentioning
confidence: 56%
“…Recently, it was shown that Lf can regulate the activation of plasminogen and control coagulation cascade with a remarkable antithrombotic activity (Zwirzitz et al, 2018). Especially this Lf property should be stressed considering that COVID-19 is a prothrombotic disease and that the severity of the coagulation parameters impairment is related to a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recently investigated effect of Lf is to regulate the activation of the plasminogen, which still adds a value of this molecule in the control of coagulation cascade promoted by the virus. LF can exert negative regulatory effects on cell migration via inhibition of Plg activation and through the regulation of fibrinolysis [85]. This activity was also confirmed by evidence of a peptide with the amino acids sequence derived from lactoferrin shown antithrombotic activity [86].…”
Section: Lactoferrinmentioning
confidence: 78%
“…These results indicate that Plg‐mediated efferocytosis occurs also in the basic human Plg‐free setup of the assay. This might be either Plg independent, or due to the bovine Plg present in serum that could have pre‐coated apoptotic bodies, since the bovine Plg molecule can also bind to human M6P/IGF2R . Further, the genetic knockout of M6P/IGF2R in phagocytes did not eliminate their efferocytic capacity completely suggesting that other receptor(s) were implicated in recognizing exposed phosphatidylserine and/or other “eat‐me” signals on apoptotic cells, or alternatively, other Plg receptors expressed on macrophages might be involved.…”
Section: Discussionmentioning
confidence: 99%